2019
DOI: 10.1021/acsami.8b19082
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Releasing Bioactive Glass Coatings and Their in Vitro Properties

Abstract: Bioactive glasses are well-known materials suitable for bone-related applications thanks to their biocompatibility and osteoconductivity. In order to improve their in vivo performance, the modification of the glass composition by adding ions with specific biological functions is required. As copper (Cu) possesses antibacterial properties, in this study, 5 wt % of CuO has been added to the 45S5 bioactive glass composition. The investigation of the effect of the Cu-containing bioactive glass on cellular behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 46 publications
0
33
0
1
Order By: Relevance
“…Metallic oxides have also been demonstrated to have antibacterial capabilities. Rau et al added 5 wt.% CuO into bioactive glass in their study and found that the CuO-contained material showed excellent antibacterial abilities, and the antibacterial abilities revealed were more effective against Gram-negative bacteria (Pseudomonas aeruginosa, Escherichia coli, and Salmonella enterica) rather than against Gram-positive bacteria (Staphylococcus aureus) [68].…”
Section: Polymer-based Coatings Combined With Antibacterial Ionsmentioning
confidence: 99%
“…Metallic oxides have also been demonstrated to have antibacterial capabilities. Rau et al added 5 wt.% CuO into bioactive glass in their study and found that the CuO-contained material showed excellent antibacterial abilities, and the antibacterial abilities revealed were more effective against Gram-negative bacteria (Pseudomonas aeruginosa, Escherichia coli, and Salmonella enterica) rather than against Gram-positive bacteria (Staphylococcus aureus) [68].…”
Section: Polymer-based Coatings Combined With Antibacterial Ionsmentioning
confidence: 99%
“…To obtain crystalline films, nanosecond PLD deposition is usually performed by the heating of the substrate or by using a buffer gas [41,44,45], so we can expect that also the deposited films are amorphous. We deposited the films at room temperature since it was demonstrated that amorphous materials show superior solubility in biological or simulated biological fluid media and are characterized by an increased bioactivity with respect to crystalline materials [8,9,29,46].…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%
“…No antibacterial effects can be expected for silicate glass films and, probably, the absence of these properties also for borate glass films can be imputed to the amount of boron released by the coatings, which could be too low to inhibit bacterial growth. Therefore, if the aim is to deposit thin bioactive films that also present antimicrobial effects, the addition of specific ions in the glass composition, such as Ag, Zn or Cu, is advisable [9,28,30,51].…”
Section: Biological Propertiesmentioning
confidence: 99%
See 2 more Smart Citations